Sistem Pakar Diagnosis Penyakit Kulit Pada Anak Menggunakan Metode Certainty Factor - Wasioh, Yustina; Lahallo, Jim (Jurnal Informatika dan Komputer, 2024)
Technological advances in the modern era have facilitated various aspects of life, including health. Puskesmas Tanjung Ria in Jayapura, Papua, Indonesia, serves about 100 patients daily from 07:30 to 14:30. One of its main services is the diagnosis of skin diseases in children, which can be caused by genetic factors, environment, stress and parasitic infections. Research shows that there are about 20 to 30 pediatric patients with skin diseases every week. Often the treatment of skin diseases is delayed due to public understanding at the Tanjung Ria Health Center, diagnosis is carried out by a team consisting of 1 doctor and 1 assistant with a symptom-based approach. However, the main obstacles are hectic work schedules and limited resources. Available pediatricians may not have enough experience in dermatology, which can lead to suboptimal treatment. To reduce uncertainty in medical diagnosis and improve the diagnosis of skin diseases in children, the Certainty Factor (CF) method is applied in the expert system. This study proposes the development of a web-based system that uses certainty factor methods for early symptoms of skin diseases in children, in order to prevent delays in treatment. System development uses the waterfall method, which includes needs analysis, design, coding and testing with the blackbox method.